ESOPHAGEAL PATHOLOGY IN SCLERODERMA SYSTEMATICA: CLINICAL AND ENDOSCOPIC FINDINGS - A E Karateev; M M Movsisyan; L P Ananyeva; S G Radenska-Lopovok (Научно-практическая ревматология)
Esophageal lesion is a characteristic visceral manifestation of scleroderma systematica (SDS). Sclerodermic esophagitis complications, such as ulcers and Barretts esophagus (BE), bring a threat to life and require active and long-term therapy. Objective: to evaluate the incidence, clinical symptoms, and endoscopic picture of esophageal pathology in patients with SDS, as well as the efficiency of therapy with proton pump inhibitors (PPIs). Subjects and methods. Three hundred and fifty-six patients (women, 92.6%; men, 7.4%) aged 47.8±19.7 years with SDS and 1018 patients (women, 89.0%; men, 11.0%) aged 44.1±16.3 years with rheumatoid arthritis (RA) were examined. Out of them, 66.7 and 52.6% took glucocorticoids (GC), 21.6 and 82.9% received nonsteroidal antiinflammatory drugs (NSAIDs), 13.2 and 0% had D-penicillamine, 15.7 and 56.5% had cytotoxic drugs, and 23.7 and 8.7% had PPIs, respectively. All the patients underwent endoscopic study of the upper gastrointestinal tract. Results. The subjective symptoms of esophageal pathology were in 64.0 and 33.9% of the patients with SDS or RA, respectively (p < 0.001). Dysphagia and retrosternal pain were observed in 10.1 and 7.0% of the patients with SDS, respectively, and in only 1.7% of the patients with RA. Endoscopy revealed mucosal hyperemia in 27.4 and 1.5% of the patients, erosive esophagitis in 21.9 and 2.2%, and esophageal ulcers in 4 (1.1%) and 0%, respectively (p = 0.000). Esophageal mucosal biopsy was performed in 92 of the 356 patients with SDS, which could identify BE (intestinal metaplasia) in 19 (20.1%) cases. There was a significant correlation between the clinical symptoms of the esophagus and the endoscopic signs of erosive esophagitis (p = 0.001). There was no relationship between esophageal pathology, age, and the use of drugs (NSAIDs, GC, cytotoxic drugs). Erosive esophagitis and BE were detected in 35.0 and 36.8% of the SDS patients (n = 90) during their regular use of PPIs. All 4 patients with esophageal ulcers regularly took PPIs. Conclusion. Esophageal pathology is noted in the majority of patients with SDS and in only individual patients with RA. BE is a common complication of SDS, which requires a regular endoscopic examinations in all patients with this disease. PPIs are not always rather effective, which determines it necessary to use large doses of these drugs or combination therapy.